Verde milho, doce milho : histórias da alimentação na Paraíba (1880 - 1920) - Paraizo, Diego Barreto (2024)
This master's thesis, developed in the Graduate Program in History, within the line of History and Regionalities at the Federal University of Paraíba (UFPB), investigates the consumption of corn and its derivatives in the interior of Paraíba. The study explores the transformations in corn consumption, the processes by which corn became a central element in the sertaneja cuisine of Paraíba, and the appropriation of corn-based foods by the Festa de São João. The work began with a detailed research in Paraíba newspapers from the late 19th and early 20th centuries. The data reveal that, from 1880 onwards, the notion of tradition associated with corn consumption began to spread significantly. Between 1880 and 1920, there was a significant increase in mentions of corn-based foods in the newspapers, indicating the beginning of a tradition that transitioned from a private context to a more public sphere. Furthermore, the study draws on references found in travelers' descriptions and historiography related to Food History. These findings are fundamental to understanding corn and corn-based foods as historical heritage, highlighting their cultural and social importance in shaping the region's culinary traditions.